Numerical Study of Flow Characteristics Across Circular Cylinders and Sliced Cylinders of Type-D and Type-I Near Flat Walls - Muhammad Azhari; Banta Cut; Nasruddin A. Abdullah (JURUTERA - Jurnal Umum Teknik Terapan, 2026)
Numerical simulations using the Ansys Fluent 2025 R2 CFD solver were conducted to investigate the unsteady and incompressible fluid flow characteristics around circular, D-type, and I-type cylinders positioned near a flat wall. The modified geometries for the D-type and I-type cylinders featured a cutting angle of 65°. This study evaluates the flow dynamics across various gap ratios (G/D) between the cylinders and the flat wall, specifically 0.05, 0.0833, and 0.1167. All simulations were performed at a Reynolds number (Re) of 5.3 using the k-SST turbulence model. The results indicate that decreasing the gap ratio triggers a significant blockage effect, characterized by flow acceleration (jetting) within the lower gap area. Qualitatively, increasing the G/D ratio is shown to delay flow separation and narrow the wake region. Visualizations of velocity and vorticity magnitude confirm that the interaction between the wall boundary layer and the cylinder's shear layer at small gaps inhibits organized vortex formation, although flow stability improves as the gap distance increases.